Extensive objectified footprints: A multidimensional approach to spatial inequalities - Gómez, Raimundo Elías (2025)
The article investigates the spatial footprints of anthropogenic emissions and infrastructures in Arcos de Valdevez, Portugal, and their association with the social composition of its parishes during the last years (2021–2023). Through the analysis of air quality, electric nightlight radiation, building age, and road networks, the research establishes connections between these physical footprints and the economic and social composition of the resident population. The study employs satellite imagery, open-access data, and the Portuguese Census of 2021 to conduct a Principal Component Analysis (PCA) and a Mixed Classification (MC), allowing for the spatial mapping of these relationships. By examining nightlight radiance intensity, road and building density, and pollutants such particulate matter (PM2.5 and PM10), nitrogen dioxide (NO2), sulphur dioxide (SO2), Carbon Monoxide (CO), ozone (O3, tropospheric), and ammonia (NH3), the study highlights the unequal distribution of physical imprints of social and economic activities shaping the environment. The findings examine the transformed environment affecting quality of life, identifying distinct classes of areas characterised by specific configurations of air pollution, infrastructure development, nocturnal electric radiance, and the social composition of residents.